Corporate Social Responsibility a contribution to development? : a study examining a major company's CSR initiative in Cape Town - Andolfi, Marco (Department of Social Development, 2014)
The following study highlights the debates around Corporate Social Responsibility (CSR) and explores to what extent the engagement of companies is contributing to development. This study focuses on one major company and its developmental activities in the Western Cape. The research is based on a main concern with the role of CSR in impoverished communities and whether CSR is contributing to development. Using a case study approach, semi-structured interviews as well as document analysis and observation have been conducted in order to achieve the research objectives.